The Precision of Lumbar Spine BMD and TBS on Different Vertebral Combinations - Promma, Sasivimol; Amnuaywattakorn, Sasithorn; Tawonwong, Tanawat; Musikarat, Suchawadee; Toengkhuntod, Ratanaporn (Biomedical Sciences and Clinical Medicine, 2024)
OBJECTIVE The objective of this study is to compute the precision and LSC of BMD and TBS at the lumbar spine using dual-energy X-ray absorptiometry in different vertebral combinations. METHODS Thirty female participants (age 58.8 ± 4.0 years, height: 155.0 ± 5.2 cm, weight: 57.4 ± 8.6 kg and BMI: 23.9 ± 3.6) were scanned at the lumbar spine twice in the same day using DXA. The precision and LSC of BMD and TBS were computed in terms of the RMS-SD and %CV using the ISCD Advanced Precision Calculation Tool. RESULTS The precision and LSC of BMD of the 4 vertebrae combinations showed the best precision and also showed a similar trend (0.005 g/cm2 and 0.62%, 0.013 g/cm2 and 1.71%), respectively. For TBS, the precision and LSC followed a similar pattern as BMD but was inferior to those of BMD. The %CV LSC of BMD for all vertebrae combinations did not exceed 5.3% as recommended by ISCD (15). The %CV LSC of TBS for 2-4 vertebrae combinations were within 5.8% with the exception of the individual vertebra which was unacceptable (%CV range 6.17-8.98). CONCLUSIONS All vertebrae combinations had an acceptable level of precision and LSC for BMD monitoring. However, the precision and LSC of TBS were inferior to those of BMD, and individual vertebra were not appropriate for TBS monitoring.